PENGARUH IKLIM ORGANISASI DAN LOYALITAS KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA PERAWAT RUMAH SAKIT IBNU SINA PEKANBARU - Fathimah Adany; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This Study aimed to describe the influence of organizational climate and job loyalty to organizational citizenship behavior at the RSI Ibnu Sina Pekanbaru. Organizational climate ²as variable (X1), job loyalty as variabel (X2), and organizational citizenship behavior as variabel (Y). The menthod in this research is descriptive and quntitative using SPSS 21, Where the sample use are 68 nurses performed byproportionate stratified random sampling method and data collection technique through questionnaires.From the results of the data analysis that includes a test of validity, reability, determination test, simple linear regression, multiple linear regression, test t, and test f.So it can be concluded that organizational climte has significant effect on organizational citizenship behavior on RSI Ibnu Sina Pekanbaru, job loyalty has significant effect on organizational citizenship behavior on nurse RSI Ibnu Sina Pekanbaru, organizational climate and job loyalty have significant effect to organizational citizenship behavior on nurse RSI Ibnu Sina Pekanbaru